Daddy's girls : a novel - Steel, Danielle (Delacorte Press, 2020)
After JT Tucker's wife died, he built the biggest ranch in California, but when he dies suddenly, the ranch is inherited by his three daughters who struggle with their differences and moving on from the loss of their dad.